2019
DOI: 10.1021/acscentsci.9b00221
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Functional Profiling of Xylan-Degrading Enzymes in Aspergillus Secretomes Using Activity-Based Probes

Abstract: Plant polysaccharides represent a virtually unlimited feedstock for the generation of biofuels and other commodities. However, the extraordinary recalcitrance of plant polysaccharides toward breakdown necessitates a continued search for enzymes that degrade these materials efficiently under defined conditions. Activity-based protein profiling provides a route for the functional discovery of such enzymes in complex mixtures and under industrially relevant conditions. Here, we show the detection and identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 53 publications
1
65
0
2
Order By: Relevance
“…Schröder et al recently carried a similar analysis of xylosidases and -xylanases in Aspergillus niger secretomes using cyclophellitol-derived ABPs. The authors demonstrated by both fluorescent labeling and proteomic analyses that A. niger secreted distinct catabolic enzymes depending on the carbon source utilized during its growth [58].…”
Section: Glycosidase Abpp For Biotechnologymentioning
confidence: 99%
See 2 more Smart Citations
“…Schröder et al recently carried a similar analysis of xylosidases and -xylanases in Aspergillus niger secretomes using cyclophellitol-derived ABPs. The authors demonstrated by both fluorescent labeling and proteomic analyses that A. niger secreted distinct catabolic enzymes depending on the carbon source utilized during its growth [58].…”
Section: Glycosidase Abpp For Biotechnologymentioning
confidence: 99%
“…Whilst monosaccharide ABPs that target retaining exoglycosidases have been relatively well explored, profiling of retaining endo-glycosidases will require more complex ABPs structures to mimic the length and/or branching of their natural substrates. Given past and recent successes in the glycosylation of fluoroglycoside [20,60], cyclophellitol-derived [58,61], and bromoketone [37] warheads, the general profiling of retaining endo-glycosidases appears to be within reach.…”
Section: Future Challenges For Glycosidase Abppmentioning
confidence: 99%
See 1 more Smart Citation
“…4). The average distance between the corresponding Asp/Glu residues in other GH3 members, as measured from the crystal structures in PDB: 1IEX [16], 2X41 [17], 3ZYZ [18], 4I3G [19], 5AE6 [to be published], and 6Q7I [20]), is approximately 13 Å.
Fig. 4Distribution of distances between the α-carbons of the catalytic residues Asp288 and Glu491 along the last 350 ns of each simulation.
…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dynamics simulations were performed on the BxlB in both its N1;5 and non-glycosylated forms using the NAMD package [56] with CHARMM36 [57] force field for proteins and carbohydrates, and TIP3P water model [58]. The BxlB structure was modeled using the I-TASSER server [59], with the PDB structure 6Q7I [20] (45.5% identity and 62.4% similarity to BxlB) as a template and further refined with the GalaxyWEB server [60]. The hydrogen atoms of the enzyme were added according to the protonation state predicted by the H++ server [61, 62] at pH 5.5.…”
Section: Methodsmentioning
confidence: 99%